Baseline abundance of Akkermansia muciniphila and Bacteroides acidifaciens in a healthy state predicts inflammation associated tumorigenesis in the AOM/DSS mouse model - Kseniya M. Achasova; Olga A. Snytnikova; Kseniya E. Chanushkina; Maryana V. Morozova; Yuri P. Tsentalovich; Elena N. Kozhevnikova (Scientific Reports)
Abstract Numerous studies demonstrate that intestinal microbiota contribute to colorectal cancer (CRC), which is often associated with dysbiosis. Most of the data were obtained from studies on CRC patients, making it challenging to determine whether alterations in microbiota are a consequence of the pathology or whether they actively drive its progression. Several studies using laboratory animals suggest that gut microbiota may be involved in both the onset and progression of CRC. In the present study we utilized the azoxymethane-dextran sulfate sodium (AOM/DSS) mouse model of CRC to investigate the contribution of healthy-state microbiota to inflammation-associated tumorigenesis. Two cohorts of C57BL/6 mice harboring different intestinal microbiota demonstrated different susceptibility to AOM/DSS treatment. Sequencing of 16S rRNA bacterial DNA from fecal samples revealed Akkermansia muciniphila and Bacteroides acidifaciens as marker features in the healthy-state microbiota (before AOM/DSS administration), which showed a strong positive correlation with tumor incidence. Moreover, the healthy-state abundance of these markers, considered beneficial bacteria, was strongly positively correlated with the sulfate-reducing bacteria Desulfovibrio fairfieldensis identified as a marker of chronic colitis-associated microbiota. Furthermore, the abundances of these marker features, associated with CRC outcome, correlated with the expression of interferon gamma and nitric oxide synthase 2 genes in colon tissue during the early stage of DSS-induced intestinal inflammation. In contrast to multiple studies demonstrating the anti-inflammatory properties of A. muciniphila and B. acidifaciens, our results point out their potential adverse effect under specific conditions of genotoxicity and inflammation in the intestine. Taken together, our findings suggest a complex, context-dependent role of commensal microbiota in inflammation-associated dysbiosis and CRC.